Analisis Tingkat Bahaya Erosi Tanah pada Kelerengan Berbeda di Perkebunan Kakao (Theobroma Cacao L.) Rakyat Kecamatan Padangguni Kabupaten Konawe - Fahrozi, Yuda; Leomo, Sitti; Zulfikar, Zulfikar; Syaf, Hasbullah; Resman, Resman; Rustam, La Ode (CV. Eduartpia Publisher, 2024)
People's cocoa plantations in Padangguni District are generally located in a steep slope topographic condition with this condition the potential for erosion is very high which can affect land productivity in the community cocoa plantation area. The purpose of this research is to predict the actual erosion rate, determine the erosion hazard index classes, and recommend soil conservation alternatives on different slopes in smallholder cocoa plantations in Padangguni Sub-District, Konawe District. This research was conducted from October to December 2022 in Padangguni Sub-District, Konawe District. The survey method was used in this research, and the prediction of erosion rates was conducted using the USLE method on 3 land units: land unit 1 located in smallholder cocoa plantations with a slope of 6% covering an area of 14.6 ha, land unit 2 with a slope of 24% covering an area of 17.2 ha, and land unit 3 with a slope of 22% covering an area of 60.5 ha. The research results showed that the highest actual erosion occurred in land unit 3 at 1,307.74 tons/ha/year, while the lowest erosion occurred in land unit 1 at 1.12 tons/ha/year. The tolerated erosion rates were 31.61 tons/ha/year for land unit 1, 25.70 tons/ha/year for land unit 2, and 26.95 tons/ha/year for land unit 3. The highest erosion hazard index was found in land unit 3 at 48.52 tons/ha/year with a very high criteria, while the lowest erosion hazard index was found in land unit 1 at 0.04 tons/ha/year with a low criteria. The recommended soil conservation techniques to ensure the sustainability of smallholder cocoa plantations include applying vegetative conservation techniques using plant residues as mulch and mechanical methods through the construction of traditional terraces or roraks. Both scenarios of soil conservation action methods can reduce the actual erosion rate, making them appropriate choices for reducing erosion rates on cocoa plantation lands